2008
DOI: 10.3174/ajnr.a1182
|View full text |Cite
|
Sign up to set email alerts
|

Histogram Analysis of MR Imaging–Derived Cerebral Blood Volume Maps: Combined Glioma Grading and Identification of Low-Grade Oligodendroglial Subtypes

Abstract: BACKGROUND AND PURPOSE:Inclusion of oligodendroglial tumors may confound the utility of MR based glioma grading. Our aim was, first, to assess retrospectively whether a histogram-analysis method of MR perfusion images may both grade gliomas and differentiate between low-grade oligodendroglial tumors with or without loss of heterozygosity (LOH) on 1p/19q and, second, to assess retrospectively whether low-grade oligodendroglial subtypes can be identified in a population of patients with high-grade and low-grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 26 publications
1
45
1
1
Order By: Relevance
“…In this study rCBV was determined by placing regions of interest over areas of highest blood volume to derive rCBV max . Subsequently elevated rCBV in association with 1p/19q loss has been supported in other small series of oligodendroglial tumours measuring rCBV [161][162][163] or using histogram analysis [164]. These data warrant further study in larger series to determine the potential of rCBV measurements for the non-invasive prediction of genotype.…”
Section: P/19q Genotypementioning
confidence: 63%
“…In this study rCBV was determined by placing regions of interest over areas of highest blood volume to derive rCBV max . Subsequently elevated rCBV in association with 1p/19q loss has been supported in other small series of oligodendroglial tumours measuring rCBV [161][162][163] or using histogram analysis [164]. These data warrant further study in larger series to determine the potential of rCBV measurements for the non-invasive prediction of genotype.…”
Section: P/19q Genotypementioning
confidence: 63%
“…There have been many reports of glioma grading using perfusion-weighted imaging, although only a few studies have dealt with the histogram method to [14,26,28,29]. Emblem et al [26] reported that the maximum peak height of the nCBV histogram was lower and exhibited a wider distribution of pixel values in HGGs, which represented the tumor heterogeneity in HGGs.…”
Section: Discussionmentioning
confidence: 98%
“…3). Several studies have investigated individual histograms in rCBV maps (25)(26)(27), but to the best of our knowledge this was the first study to compare mean histograms of 18 F-FET PET and rCBV maps in gliomas.…”
Section: Discussionmentioning
confidence: 99%